Studying Lived Religion: Contexts and Practices, by NANCY TATOM AMMERMAN - Hall, David D. (Sociology of religion, 2022)
Generous in spirit and substance, Studying Lived Religion is akin to a handbook-cum-manifesto animated by Nancy Ammerman’s enthusiasm for a "lived" or "practice